2008
DOI: 10.1128/aem.02702-07
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fumarase C and NADH Oxidase in Metabolic Adaptation ofPseudomonas fluorescensCells Evoked by Aluminum and Gallium Toxicity

Abstract: Iron (Fe) is a critical element in all aerobic organisms as it participates in a variety of metabolic networks. In this study, aluminum (Al) and gallium (Ga), two Fe mimetics, severely impeded the ability of the soil microbe Pseudomonas fluorescens to perform oxidative phosphorylation. This was achieved by disrupting the activity and expression of complexes I, II, and IV. These toxic metals also inactivated aconitase (ACN) and fumarase A (FUM A), two tricarboxylic acid cycle enzymes dependent on Fe for their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 37 publications
4
38
1
Order By: Relevance
“…This metabolite aided by the enzymes ME and ICDH-NADP, may allow P. fluorescens to battle the oxidative challenge posed by H2O2. Indeed, various organisms are shown to evoke intricate NADPH-generating pathways to modulate their NADPH budget to combat oxidative stress Chenier et al, 2008;Drummond et al, 2011;Spanier et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This metabolite aided by the enzymes ME and ICDH-NADP, may allow P. fluorescens to battle the oxidative challenge posed by H2O2. Indeed, various organisms are shown to evoke intricate NADPH-generating pathways to modulate their NADPH budget to combat oxidative stress Chenier et al, 2008;Drummond et al, 2011;Spanier et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, oxidative phosphorylation is downregulated as revealed by the diminished activity of Complex I, a situation that may impede the generation of 28 NAD. To rectify such an occurrence, the microbe invokes the participation of NADH oxidase, an enzyme whose activity is known to be increased during environmental stress (Chenier et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Chenier et al found that as a consequence of the pronounced stress in the presence of Ga or Al, P. fluorescens responds with active reorganization of its metabolic pathways to use the tricarboxylic acid (TCA) cycle (12,32). At present, it is not known whether pathogenic bacteria possess similar mechanisms and how the presence or absence of such mechanisms can affect their virulence.…”
mentioning
confidence: 99%
“…It has been shown that Ga and another Fe mimetic, Al, have severe toxicity for Pseudomonas fluorescens, impeding the functionality of the electron transport chain and enzymes containing Fe-S clusters (12). Chenier et al found that as a consequence of the pronounced stress in the presence of Ga or Al, P. fluorescens responds with active reorganization of its metabolic pathways to use the tricarboxylic acid (TCA) cycle (12,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation